Hierarchical TiO2 microspheres composed with nanoparticle-decorated nanorods for the enhanced photovoltaic performance in dye-sensitized solar cells. Issue 6 (23rd January 2019) - He, Xiong; Zhang, Jingyu; Guo, Yan; Liu, Jinghua; Li, Xin
Abstract : Hierarchical NP-MS combines the beneficial properties of improved scattering capability, dye loading ability, electron transport and inhibited charge recombination. The photoelectric conversion efficiency up to 7.32% has been obtained. Abstract : Hierarchical TiO2 microspheres composed of nanoparticle-decorated nanorods (NP-MS) were successfully prepared with a two-step solvothermal method. There were three benefits associated with the use of NP-MS as a photoanode material. The decoration of nanoparticles improved the specific surface area and directly enhanced the dye loading ability. Rutile nanorods serving as electron transport paths resulted in fast electron transport and inhibited the charge recombination process. The three-dimensional hierarchical NP-MS structure supplied a strong light scattering capability and good connectivity. Thus, the hierarchical NP-MS combined the beneficial properties of improved scattering capability, dye loading ability, electron transport and inhibited charge recombination. Attributed to these advantages, a photoelectric conversion efficiency of up to 7.32% was obtained with the NP-MS film-based photoanode, resulting in a 43.5% enhancement compared to the efficiency of the P25 film-based photoanode (5.10%) at a similar thickness. Compared to traditional photoanodes with scattering layers or scattering centers, the fabrication process for single layered photoanodes with enhanced scattering capability was very simple. We believe the strategy would be beneficial for the easy fabrication of efficient dye-sensitized solar cells.